Theodor Storm$1 (Bs Novellen : Essays on Literary Techniques - McCormick, E. Allen (Chapel Hill The University of North Carolina Press, 1964)
These six essays elucidate some of the more significant aspects of Storm's literary technique. The treatments of some of Storm's "Novellen", including "Am Kamin", "Aquis Submersus" and two versions of "Immensee", show how Storm used structure, symbolism, elements of tragedy and other narrative devices in his prodigious body of works of German Realism.
National Endowment for the Humanities
Andrew W. Mellon Foundation
English
Keywords: Literature: history & criticism; German Studies; Literature